Factors of progressive development in food industry - Tymofeev, Konstantin; Savchuk, Andriy (My University, 2014)
Dynamics and regularities of development of the consumer’s food market continues to exert a strong influence on the growth and change of the product’s structure of the industry of food ingredients, raw materials, additives, assistive technology equipment, flavors and concentrates.
Keywords: development; solution; manufacture; розвиток; рішення; виробництво; развитие; решение; производство; кафедра іноземних мов професійного спрямування